Critical Analysis of the School Curriculum in Chile Based on Social Justice - Mujica-Johnson, Felipe Nicolás (2020)
School education in Chile is composed of a curriculum that essentially responds to a positivist approach, called pedagogy by objectives. Therefore, school children are classified according to their academic performance and are prepared to compete in different standardized tests, which are conditioned to economic stimuli and the opportunity to continue their studies in higher education. Given this situation, this essay aimed to critically analyze the learning objectives and the evaluation of the Chilean school curriculum in terms of the perspective of social justice. At the beginning of the analysis, the inadequate standardization of the curriculum is described since ambiguity characterizes the learning objectives, and in terms of summative evaluations, there are no clear ministerial guidelines. Thus, it is argued that this produces unequal competition among students, teachers, and different educational centers. However, it is identified that to continue standardizing the curriculum is not appropriate; instead, the school curriculum logic must make an epistemological turn towards a constructivist and sociocritical perspective. In this way, it will be possible to progress towards an emancipatory education that works for social justice.